Religious Tourism in Northern Thailand : Encounters with Buddhist Monks - Schedneck, Brooke (Book collections on Project MUSE., 2021)
"Temples are everywhere in Chiang Mai, filled with tourists as well as saffron-robed monks of all ages. The monks participate in daily urban life here as elsewhere in Thailand, where Buddhism is promoted, protected, and valued as a tourist attraction. Yet this mountain city offers more than a fleeting, commodified tourist experience, as the encounters between foreign visitors and Buddhist monks can have long-lasting effects on both parties. These religious contacts take place where economic motives, missionary zeal, and opportunities for cultural exchange coincide. Brooke Schedneck incorporates fieldwork and interviews with student monks and tourists to examine the innovative ways that Thai Buddhist temples offer foreign visitors spaces for religious instruction and popular in-person Monk Chat sessions in which tourists ask questions about Buddhism. Religious Tourism in Northern Thailand also considers how Thai monks perceive other religions and cultures and how they represent their own religion when interacting with tourists, resulting in a revealing study of how religious traditions adapt to an era of globalization"--